GRAMMAR ERRORS IN ACADEMIC WRITING IN ENGLISH: CAUSES AND STRATEGIES OF CORRECTION - O. L. Dobrynina (Высшее образование в России, 2017)
The article addresses the influence of interference on errors and mistakes in academic writing made by students earning their Master's degrees in math and physics. The author briefly characterizes types of interference and errors, and analyzes the effect of the Russian language grammar when students transfer specifically Russian patterns to the English language. Students face problems when dealing with the structure of the English sentence and word order, tense system and active and passive voices, articles and prepositions. The author provides examples of common grammar errors and mistakes caused by students' mother tongue interference. Special attention is paid to the ways of preventing such errors and to teaching students to recognize and correct errors on their own.